IMPLEMENTASI KALENDER BATAK (PARHALAAN) PADA ADAT BATAK - Frifana, Sherly Olyfiya (UIN ALAUDDIN MAKASSAR, 2022)
The purpose of this study, in order to know about the Batak calendar. This Batak calendar is a local calendar related to various Batak people's lives, such as religious ceremonies, wedding ceremonies, death ceremonies, farming, sowing seeds, and also determining good days and bad days. This writing methodology, obtained from library research, by collecting sources through books, journals, theses, websites and articles related to the discussion of the Batak Calendar. With qualitative data collection methods, with primary data supporting sources of books and journals, with secondary data in the form of theses, websites and articles. The results show that this Batak tribe, has a characteristic of its calendar or what is called parhalaan with various urgencies that exist. So this Batak calendar, as a benchmark in the life of the Batak people. Keywords: History of Parhalaan, Names of Parhalaan, Urgency of Parhalaan